2014
DOI: 10.7243/2049-9752-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal intubation and outcome in high-risk patients with acute myocardial infarction undergoing primary angioplasty

Abstract: Background: Patients with acute myocardial infarction (AMI) who undergo endotracheal intubation (ETI) are at high risk for mortality, but the outcome of those patients submitted to primary angioplasty (PCI) has not yet clearly reported. Methods:We collected data about all consecutive patients with AMI within 12 hours who underwent primary PCI and analyzed clinical and procedural characteristics as well as in-hospital mortality of ETI compared to no-ETI patients. Results: From September 2001 to June 2010, 1251… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The requirement for endotracheal intubation was mainly due to acute pulmonary congestion. The previous study has shown that intubated patients with ACS who underwent pPCI had a higher in-hospital mortality rate than non-intubated patients [ 29 ]. The worsening of in-hospital prognosis in intubated patients can result from both the pathophysiologic changes due to intubation and ventilation [ 30 ] and the severity of acute heart failure and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for endotracheal intubation was mainly due to acute pulmonary congestion. The previous study has shown that intubated patients with ACS who underwent pPCI had a higher in-hospital mortality rate than non-intubated patients [ 29 ]. The worsening of in-hospital prognosis in intubated patients can result from both the pathophysiologic changes due to intubation and ventilation [ 30 ] and the severity of acute heart failure and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%